Effect of Green Nuts (Vigna radiata L.) Extract on Blood Hemoglobin (Hb) Levels in Adolescent Women During Menstruation - Yesi Dian Pratiwi; Dian Priharja Putri (STIKep PPNI Jawa Barat, 2023)
Aims: The most common nutritional problem in adolescents, especially young women, is iron deficiency or anemia. The World Health Organization (WHO) in 2015 reported that more than 30% or 2 billion adolescents in the world are anemic and in developing countries, one of them is Indonesia. Riskesdas data (2018) shows 32% have anemia in the 15-24 year age group. The cause of anemia is due to lack of iron and the impact of anemia is stunted growth, the body is susceptible to infection, reduced body fitness, and decreased enthusiasm for learning. Mung bean essence is a drink that contains 13.41 mg of iron in 100 gr/100 ml. Objective: To analyze the effect of green bean extract (Vigna radita L.) on blood hemoglobin (Hb) levels during menstruation in female adolescents at SMA Negeri I Ketapang Method: Pre-experimental design with one group pre-post test. The sampling technique used a purposive sample, namely 44 young women at SMA N 1 Ketapang. Data analysis with Wilcoxon test Results: Hb levels before being given mung beans, the average value was 11.31 gr/dL, the lowest Hb level was 9 and the highest was 13. Meanwhile, after being given mung beans, the average respondent's Hb level was 12.90 gr/dL with the lowest level is 11 gr/dL and the highest is 14 gr/dL. The results of the Wilcoxon test found a p-value of 0.000 <0.05 meaning that there was an effect of giving green bean extract (Vigna Radita L.) on blood hemoglobin (Hb) levels during menstruation in young women at SMA Negeri I Ketapang. Conclusions : mung bean extract affects the Hb level of female adolescents during menstruation. It is hoped that teenagers can use mung bean extract as an option in an effort to increase Hb to prevent anemia in adolescents, especially young women.